answersLogoWhite

0

6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)



6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)



6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)



6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)
User Avatar

Wiki User

12y ago

Still curious? Ask our experts.

Chat with our AI personalities

SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve
MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
EzraEzra
Faith is not about having all the answers, but learning to ask the right questions.
Chat with Ezra
More answers

6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)

User Avatar

Wiki User

12y ago
User Avatar

Add your answer:

Earn +20 pts
Q: What does 6x squared plus 35xy plus 11y squared equal?
Write your answer...
Submit
Still have questions?
magnify glass
imp